FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BRUNO, KABUPATEN PURWOREJO, JAWA TENGAH - Mirani, Mila; Utami, Ni Wayan Arya (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p13, 2025)
ABSTRACT The incidence of CED for pregnant women at the Bruno Health Center in 2022 is 15.7%, the highest in Purworejo Regency, so an analysis is needed to reduce the risk of death and low birth weight. The purpose of this study was to determine the factors related to the incidence of CED and the differences in the consumption levels of energy, protein and iron in pregnant women with CED and not CED in the Working Area of ??the Bruno Health Center, Purworejo Regency, Central Java.This research is an analytic observational study with a case control design. The total sample in this study was 76 pregnant women consisting of 38 case samples and 38 control samples who were selected at simple random from the cohort of pregnant women in March 2023. The variables studied were age, education, income, birth spacing, knowledge, and level of difference consumption of energy, protein and iron. Data was collected directly using a questionnaire. The results of the analysis showed that there were factors related to the incidence of CED, namely income (p=0.018) and knowledge (p=0.013), while factors that were not related were age (p=0.103), education (p=0.076), birth spacing (p = 0.773). There were differences in energy consumption levels (p=0.001), protein consumption levels (p=0.004), and iron consumption levels (p=0.001) among pregnant women with CED and not CED. Keywords : Pregnant women, Knowledge, Consumption level